Candidatus Liberibacter asiaticus Titers in Citrus and Acquisition Rates by Diaphorina citri Are Decreased by Higher Temperature - Lopes, S. A.; Luiz, F. Q. B. F.; Martins, E. C.; Fassini, C. G.; Sousa, M. C.; Barbosa, J. C. [UNESP]; Beattie, G. A. C. (Amer Phytopathological Soc, 2013)
Candidatus Liberibacter asiaticus' is the most prevalent Liberibacter sp. associated with huanglongbing (HLB) in Brazil. Within Sao Paulo state (SP), HLB has spread more rapidly to and reached higher incidence in regions with relatively mild (cooler) summer temperatures. This suggests that climate can influence disease spread and severity. 'Ca. L. asiaticus' titers on soft, immature leaves from infected 'Valencia' sweet orange plants exposed to different temperature regimes and adult Diaphorina citri fed for 48 h on these plants for 'Ca. L. asiaticus' acquisition were determined by quantitative polymerase chain reaction in two experiments. The first experiment included plants with three levels of infection, three incubation periods (IPs), and air temperatures favorable (14.6 to 28 degrees C) and unfavorable (24 to 38 degrees C) to 'Ca. L. asiaticus'. The second included plants with severe late-stage infections, 10 IPs (based on 3-day intervals over 27 days), and three air temperature regimes (12 to 24, 18 to 30, and 24 to 38 degrees C). Overall, 'Ca. L. asiaticus' titers and the percentages of 'Ca L asiaticus'-positive psyllids were lower in plants maintained at the warmer temperature regime (24 to 38 degrees C) than in plants maintained in the cooler regimes. The results suggest that the lower incidence and slower spread of 'Ca. L. asiaticus' to warmer regions of SP are related to the influence of ambient temperatures on titers of 'Ca. L. asiaticus' in leaves.